Pneumothorax in adults with cystic fibrosis dependent on nasal intermittent positive pressure ventilation (NIPPV): a management dilemma. Issue 7 (1st July 2000) - Haworth, C S; Dodd, M E; Atkins, M; Woodcock, A A; Webb, A K
Abstract : The management of pneumothorax in three adult patients with cystic fibrosis dependent on nasal intermittent positive pressure ventilation is described.